Assistive Technology for Students with Visual Impairments: A Path Revisited - Dawn, Dr Ranjita (INDIAN EDUCATIONAL REVIEW, 2012)
The paper aims to look at the significance of assistive technologies for the education of persons with visual impairments. In this context, it makes an attempt to analyse some of the benefits of assistive technologies and their usage for providing a quality education to such people. It also provides a critical review of the limitations of such technologies that needs to be addressed to facilitate their better instruction and integration.